203k views
2 votes
4−5(1 r) −2 = 3 +6r solve for r

User Juancentro
by
5.3k points

1 Answer

7 votes

Answer:


r=-(1)/(11)

Explanation:


4-5(1r) -2 = 3 +6r\\\\\mathrm{Remove\:parentheses}:\quad \left(a\right)=a\\\\4-5r-2=3+r\\\\\mathrm{Group\:like\:terms}\\\\-5r+4-2=3+6r\\\\-5r+2=3+6r\\\\\mathrm{Subtract\:}2\mathrm{\:from\:both\:sides}\\-5r+2-2=3+6r-2\\\\Simplify\\-5r=6r+1\\\\\mathrm{Subtract\:}6r\mathrm{\:from\:both\:sides}\\-5r-6r=6r+1-6r\\\\Simplify\\\\-11r=1\\\\\mathrm{Divide\:both\:sides\:by\:}-11\\\\(-11r)/(-11)=(1)/(-11)\\\\Simplify\\\\r=-(1)/(11)

User Oscar Mederos
by
5.8k points